Statistical ideas and methods - Utts, Jessica M.; Heckard, R. F. (Belmont, CA : Thomson-Brooks/Cole, 2006)
Student CD-ROM contains lab manuals, applets, data sets, presentation slides, Web resources, and tutorial quiz; Interactive video skillbuilder CD-ROM contains video instruction on key examples from the text.
Keywords: Statistics